Relationship between Neutrophil to Lymphocyte Ratio (NLR) and Gensini Score in Patients with Coronary Artery Disease (CAD) at Mataram City General Hospital: A Cross Sectional Study - Ni Putu Emi Januantari; Deasy Irawati; Basuki Rahmat (Cardiovascular and Cardiometabolic Journal (CCJ), 2023)
Highlights: It discusses the relationship between NLR and the severity of coronary atherosclerosis. There is significant difference from the previous NLR research Abstract: Background. Neutrophil to Lymphocyte Ratio (NLR) is a marker of systemic inflammation correlated with the incidence of Coronary Artery Disease (CAD). Neutrophils infiltrate the coronary artery plaque causing acceleration of atherosclerosis. T lymphocyte recruitment is required at the early stages of plaque formation. Previous studies have shown that heightened NLR was correlated with the percentage of stenosis at the site of the multivessel lesion. Aims. This study aimed to determine the relationship between NLR with Gensini score of coronary arteries in CAD patients at Mataram City General Hospital. Material and method. This was a cross sectional study conducted in Mataram City General Hospital. Fifty-nine patients diagnosed with CAD participated in the study. Blood collection and coronary angiography were performed to assess NLR and Gensini Score. The main variables were NLR and Gensini Score. Gensini score of 1-29 was considered as mild atherosclerosis and Gensini score of 30 or more was considered as severe atherosclerosis. NLR was considered high if the value of NLR were > 2.385 based on previous studies. Spearman test was performed to assess correlation between variables. Results. Approximately 53% subjects were categorized as severe atherosclerosis and 48% as mild atherosclerosis. The median values of Gensini score in the low NLR group were 25.0 and in the high NLR group were 40.0 (p=0,19). The median values of NLR in the mild group of atherosclerosis were 1.78 and in the severe atherosclerotic group were 2.15 (p=0,59). There was no significant difference in NLR between severe atherosclerosis and mild atherosclerosis groups. NLR was not associated with Gensini score (p=0,32). Conclusions. There was no significant relationship between Neutrophil to Lymphocyte Ratio with Gensini score of coronary arteries in CAD patients at Mataram City General Hospital.